Contribution of Terminalia catappa l. to the survival of Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) in Bujumbura City, Burundi - Lievin, Ndayizeye; Claver, Sibomana (International Research Journal of Insect Sciences, 2023)
The research aimed at showing the contribution of Terminalia catappa to the survival of B. dorsalis. Through fruit incubation, the study was done in Bujumbura city from June to September 2017. Individuals were collected from fruits infested by flies. Fruits were collected in neighborhoods according to the population and fruit trees density. Results show that T. catappa was infested by two species B. dorsalis and C. cosyra with very low numbers. B. dorsalis was abundant in the neighborhoods with low population density and high number of fruit trees. The latter have higher infestation rates than those with high population density and few number of fruit trees. This study showed that T. catappa contributes significantly to the survival of populations of B. dorsalis in Bujumbura city as the latter uses its fruits as host especially in the dry season. T. catappa can be considered an alternative host plant for B. dorsalis used in the absence of its preferred host plants. Practical implications of this research is the use of orchard sanitation for eradicating B. dorsalis.